Susceptibility of Neisseria gonorrhoeae to azithromycin and ceftriaxone in China: A retrospective study of national surveillance data from 2013 to 2016 - Yin, Yue-Ping (PLoS Med, 2018)
BACKGROUND: Gonorrhea remains one of the most common sexually transmitted diseases worldwide. Successful treatment has been hampered by emerging resistance to each of the antibiotics recommended as first-line therapies. We retrospectively analyzed the susceptibility of gonorrhea to azithromycin and ceftriaxone using data from the China Gonococcal Resistance Surveillance Programme (China-GRSP) in order to provide evidence for updating the treatment recommendations in China. METHODS AND FINDINGS: In this study, we included 3,849 isolates collected from patients with a confirmed positive Neisseria gonorrhoeae (N. gonorrhoeae) culture at clinic visits during the period of 1 January 2013 through 31 December 2016 in 7 provinces. Antimicrobial susceptibility testing of gonorrhea isolates using agar dilution was conducted to determine minimum inhibitory concentration (MIC). Resistance to azithromycin (RTA) was defined as MIC ≥ 1.0 mg/l, and decreased susceptibility to ceftriaxone (DSC) was defined as MIC ≥ 0.125 mg/l. The prevalence of isolates with RTA was 18.6% (710/3,827; 95% CI 17.4%–19.8%). The percentage of patients with DSC fluctuated between 9.7% and 12.2% over this period. The overall prevalence of isolates with both RTA and DSC was 2.3% (87/3,827; 95% CI 1.9%–2.8%) and it increased from 1.9% in 2013 to 3.3% in 2016 (chi-squared test for trend, P = 0.03). Study limitations include the retrospective study design and potential biases in the sample, which may overrepresent men with symptomatic infection, coastal residents, and people reporting as heterosexual. CONCLUSIONS: To our knowledge, this is the first national study on susceptibility of N. gonorrhoeae to azithromycin and ceftriaxone in China. Our findings indicate high rates of RTA and DSC from 2013 to 2016. Although dual therapy with azithromycin and ceftriaxone has been recommended by WHO and many countries to treat gonorrhea, reevaluation of this therapy is needed prior to its introduction in China.